Regioselective synthesis of spirobarbiturate-dihydrofurans and dihydrofuro[2, 3-d]pyrimidines via one-pot cascade reaction of barbiturate-based olefins and ethyl acetoacetate. (22nd January 2021) - Liu, Songtao; Shao, Pei; Li, Yanli; Wang, Donghao; Hou, Deshan; Qu, Chaofan; Song, Xixi; Yan, Xuebin
Abstract: Michael addition initiated ring closure reaction of barbiturate-base olefins and ethyl acetoacetate with NBS has been explored. Spirobarbiturate-dihydrofuans and dihydrofuro[2, 3- d ]pyrimidines were regioselectively synthesized via one-pot cascade reactions in the presence of DBU or potassium carbonate, respectively. Graphical abstract: Image 1 Highlights: Regioselective synthesis of spirobarbiturate-dihydrofurans via DBU-promoted one-pot cascade reaction. A high-yield regioselective method for synthesis of spirobarbiturate-dihydrofuran was demonstrated. Selective synthesis of dihydrofuro[2, 3- d ]pyrimidine promoted by Potassium carbonate. Transition metal free in the reaction. Mild reaction condition.